Accessibility Evaluation of University Websites in Indonesia based on WCAG 2.2 Guidelines - Ketut Dian Suryasih; Putu Yudia Pratiwi; I Made Ardwi Pradnyana (SISTEMASI, 2026)
Universities use websites as their main portal and main source of information. However, some university websites in Indonesia still show accessibility issues and do not meet the Web Content Accessibility Guidelines (WCAG) 2.2 standards. This research aims to evaluate the accessibility of five university websites in Indonesia based on the Similarweb platform. The evaluation focused on color blindness, attention deficit, and limited movement. These three disabilities are considered to have a significant impact on web accessibility. The method used in this study was WCAG-EM by using a combination of automated and manual evaluation. The automated evaluation used WAVE and Siteimprove Accessibility Checker tools. Meanwhile, manual evaluation adopted the evaluation steps from the Accessibility Insights tool by Microsoft. The results of the automated evaluation showed that the accumulated issues obtained from all university homepages were 188 issues. There are 7 types of issues identified through manual evaluation. The most common accessibility issue found is components with low contrast between the foreground and background. These results indicate that university websites in Indonesia, based on Similarweb rankings, still do not meet the international standards WCAG.